Congenital angular deformities of the leg : congenital pseudoarthrosis and congenital posteromedial angulation of the tibia (Annals of Medical Research, 2021)
None
Keywords: s : Congenital angular deformity, tibia, anterolateral angulation, pseudoarthrosis